The Communicative Approach in Teaching English - Wankong, Anchanida (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
Now, communicative approach has become a popular method of studies especially for a study of English as a second language. Teacher needs to design teaching way approach which can be developed students’ communicative competence.  Mainly the language classroom of English as a second language encounters with uninteresting students in learning English because they rarely practice English in classroom. Moreover, uninteresting activities were brought into the classroom without any inspiration. Therefore the writer was interested in communicative approach in teaching English. Using language activities can be used for developing the students in language’s practice and self-learning. The outcome of language competence is not only the ability of using English in communication in daily life but also the positive attitude is the results of studying English as a second language.